Molar Incisor Hypomineralisation: A Recent Condition or a New Perception? - Santos-Pinto, Lourdes [UNESP]; Rios, Daniela (My University, 2024)
The condition known as molar incisor hypomineralisation (MIH) has been featured in the dental literature for some time. However, the condition itself, characterized by demarcated opacities, had been observed and documented in various forms before the official terminology was coined. The awareness and understanding of MIH have increased over the years, and there has been ongoing research to explore its prevalence, etiology, clinical implications, care, and treatment. In summary, MIH is not a recent condition, but the terminology and recognition of this dental phenomenon have been refined and formalized in the relatively recent past. This chapter reflects on our clinical experience, juxtaposing it with information from scientific literature and personal insights, as well as identifying gaps in understanding this enamel defect. Furthermore, another aim was to foster contemplation for potential research advancements in the MIH field.